School Psychological Environment and Learning Burnout in Medical Students: Mediating Roles of School Identity and Collective Self-Esteem - Yu, Wanwan; Yang, Shuo; Chen, Ming; Zhu, Ying; Meng, Qiujian; Yao, Wenjun; Bu, Junjie (Frontiers in Psychology, 2022)
Learning burnout is an important indicator that reflects an individual's learning state. Understanding the influencing factors and mechanism of learning burnout of medical students has practical significance for improving their mental health. This study aimed to explore the mediating roles of school identity and collective self-esteem between school psychological environment and learning burnout in medical students. A total of 2,031 medical students (942 men and 1089 women, age range: 17–23 years) were surveyed using the School Psychological Environment Questionnaire (SPEQ), School Identity Questionnaire (SIQ), Collective Self-esteem Scale (CSES), and Learning Burnout Scale (LBS). The results showed the following: (1) school psychological environment had a negative effect on learning burnout among medical students (β=-0.19, p<0.001), and (2) school identity and collective self-esteem played significant mediating roles between school psychological environment and learning burnout [(95% CI = (-0.43, -0.31)]. Specifically, there were three paths that school psychological environment and learning burnout: first, through the independent mediating role of school identity; second, through the independent mediating role of collective self-esteem; and third, through the chain mediating roles of school identity and collective self-esteem. The findings reveal that school psychological environment not only directly influences the learning burnout of medical students but also indirectly influences it through school identity and collective self-esteem. Thus, this study has some important implications for prevention and intervention of learning burnout among medical students.